Actividades lúdicas y su incidencia en el aprendizaje en estudiantes del quinto año de EGB de la UE “Juan E. Verdesoto”, Babahoyo. 2022 - Acosta Rojas, Susana Jamileth (2023)
Recreational activities are strategic tools that are intended to motivate children to learn, this research work was developed with the participation of fifth-year students of parallel basic general education "B" of the educational unit Juan E. Verdesoto, through the use of the analytical, deductive-inductive method and with the bibliographical research that served as the basis for the theoretical support of the variables, with which their incidence in learning was studied. By involving recreational activities in the classroom, it is intended to improve the teaching process in order for students to achieve good academic performance, achieving that through its application the objectives set in education are achieved. It is extremely important to put the games into practice in order to facilitate the understanding of the contents presented in the educational texts of each of the basic areas constituted in the curriculum, which help students develop their skills, abilities, competencies, stimulating creativity, motivation and participation in the classroom to encourage the construction of knowledge. Reaching achievements in learning depends on the planning of activities carried out by the teacher, becoming tools that allow problem solving such as the construction of concepts through experiences and interaction with others, to capture the interest of the topics is It is necessary that the games are established according to the educational contents.